Návrh na zlepšení hospodaření obce Vacenovice - Čiráková, Alexandra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce je zaměřena na celkové zlepšení rozpočtu obce Vacenovice ve vztahu k celkovému hospodaření obce, jejímu postavení a pravomocem. Práce je rozdělena do několika částí, které obsahují teoretická východiska, základní charakteristiku obce Vacenovice, analýzu příjmů a výdajů obecního rozpočtu za poslední roky a v poslední části jsou předloženy návrhy na zlepšení hospodaření obce.

The master’s thesis is focused on general improvement of Vacenovice municipality’s budget in relation to overall management of the municipality, its position and competence. The thesis is divided into several parts, including the theoretical background, basic characterization of the municipality Vacenovice, analysis of income and expenditures of the municipality budget in recent years, and in the last part, proposals to improve management of the municipality.
The Proposal for Economy Improvement of Municipality of Vacenovice
Keywords: Rozpočet; Obec; Samospráva; Příjmy a výdaje; Rozpočtová soustava; Hospodaření obce.; Budget; Municipality; Self-government; Receipts and expenditures; Budgetary scale; Financial management of municipality.